2000
DOI: 10.1007/s002590050556
|View full text |Cite
|
Sign up to set email alerts
|

Detection of somatostatin receptor-positive tumours using the new 99m Tc-tricine-HYNIC- d -Phe 1 -Tyr 3 -octreotide: first results in patients and comparison with 111 In-DTPA- d -Phe 1 -octreotide

Abstract: Indium- 111 labelled DTPA-D-Phe1-octreotide (DTPA-OC, OctreoScan) has been introduced into clinical routine for the detection of somatostatin receptor (SSTR)-positive tumours, which are predominantly of neuroendocrine origin. Potential further applications in other SSTR-positive cancers (e.g. small cell lung cancer, breast cancer, melanoma) have been limited mainly by the restricted availability and the high radionuclide costs. Previous attempts to introduce technetium-99m labelled analogues of octreotide have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…The uptake of the two tracers is comparable (12). Because of these characteristics, we chose to evaluate these patients with this modality, thus reducing radiation exposure and scanning time and increasing the accuracy and sensitivity of lesion detection.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of the two tracers is comparable (12). Because of these characteristics, we chose to evaluate these patients with this modality, thus reducing radiation exposure and scanning time and increasing the accuracy and sensitivity of lesion detection.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the coligand has a significant impact on both the tumor accumulation and the biodistribution of 99m Tc complexes. For example, the binary ligand 99m Tc complex [ 99m Tc(HYNIC-TOC)(tricine) 2 ] shows much higher protein binding than the complexes [ 99m Tc(HYNIC-TOC)(EDDA) x ] and [ 99m Tc(HYNIC-TOC)(tricine) (NIC)] [21][22][23][24][25]. The high serum protein binding was also observed for the 99m Tc-labeled DNA oligonucleotides when tricine was used as the coligand [29][30][31].…”
Section: Effect Of Coligand On Physical and Biological Properties Of mentioning
confidence: 99%
“…Since then, the HYNIC technology has successfully been used for the 99m Tc-labeling of antibodies [3][4][5][6][7][8] and small biomolecules (BMs), including chemotactic peptides [9][10][11][12][13][14][15][16][17][18], somatostatin analogs [19][20][21][22][23][24][25],"stealth" liposomes [26,27], antisense oligonucleotides [28][29][30][31], a folate receptor ligand [32], and polypeptides [32][33][34]. A ternary ligand system (HYNIC, tricine, and trisodium triphenylphosphine-3,3¢,3≤-trisulfonate, TPPTS) has been used for the 99m Tc-labeling of chemotactic peptides [35] and leukotriene B 4 (LTB 4 ) receptor antagonists [36][37][38][39] for imaging infection and inflammation, integrin a v b 3 receptor antagonists for tumor imaging [40], and a glycoprotein IIb/IIIa (GPIIb/IIIa) receptor antagonist for imaging thrombosis [41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…It is thus a very attractive target for the imaging of growing tumors. Several metalbased agents have been developed for the imaging of integrin expression using PET ( 64 Cu) or SPECT ( 99m Tc, 111 In) radionuclides [56][57][58][59][60][61][62][63][64]. All of these agents share a similar design, using the same peptide-based targeting vector-the sequence arginine-glycine-aspartic acid (RGD), which binds avidly to α v β 3 integrins-combined with chelators for radionuclide binding.…”
Section: Angiogenesismentioning
confidence: 99%
“…All of these agents share a similar design, using the same peptide-based targeting vector-the sequence arginine-glycine-aspartic acid (RGD), which binds avidly to α v β 3 integrins-combined with chelators for radionuclide binding. In particular, HYNIC-RGD peptide conjugates are used with 99m Tc and DOTA-RGD conjugates are used for the PET isotopes 64 Cu and 98 Ga as well as for 111 In for SPECT. Overall, all these agents show high α v β 3 -positive tumor uptake together with fast blood clearance and renal excretion.…”
Section: Angiogenesismentioning
confidence: 99%